Batasan Kompetensi Absolut Pengadilan Agama (Analisis Putusan Peninjauan Kembali Nomor 672 PK/Pdt/2016) - Arditio Dwianto; Nurul Hanani; Hizbulloh Hadziq (MAHAKIM Journal of Islamic Family Law, 2022)
In adjudicating a case, the court as the executor of judicial power of course sees whether it has the authority to adjudicate the case submitted by the plaintiff based on the absolute competence of each court within a particular judicial institution. However, in practice, there are courts in the general judiciary which consider the case being submitted by the plaintiff to be their authority, even though when referring to the applicable provisions, the case submitted by the plaintiff is essentially a case whose authority lies with the court in the religious court institution. This study discusses how the legal considerations of judges are based and how the judges' decisions match the absolute competence limits of religious courts in the Judicial Review Decision Number 672 PK/Pdt/2016. This study uses a normative legal research type by using a law approach and a case approach in analyzing legal problems. The results of this study can be concluded as follows: First, in the consideration of the panel of judges in the court of first instance until the cassation, there was an error in applying the law in which the panel of judges was fixated on the title of the lawsuit against the law which actually the substance of the lawsuit is an inheritance case between people who are Muslims who are under the authority of the Kediri Regency Religious Court, not the Kediri Regency District Court. Second, the decision of the panel of judges which stated that the district court was not authorized to hear the case in the Judicial Review Decision Number 672 PK/Pdt/2016 was in accordance with the absolute competence limit of the religious court.